Family Support in the Emotional Well-being of Cancer Patients - Agrawal, Shruti (Disease and Health: Research Developments Vol. 9, 2025)
Cancer is a life-altering disease that not only affects patients physically but also has profound emotional and psychological consequences. The presence of a strong support system, particularly from family members, has been recognized as a key factor in improving patient outcomes. This chapter explores the significance of family involvement in cancer care, emphasizing how emotional well-being contributes to treatment adherence and overall recovery. Research indicates that patients who receive consistent familial support exhibit lower levels of stress, anxiety, and depression, which, in turn, positively impacts their immune response and coping mechanisms. Additionally, the role of healthcare providers in fostering family participation is examined, highlighting both the benefits and challenges of integrating family members into the care process. The chapter also discusses structured interventions, such as family counseling, support groups, and education programs, aimed at equipping caregivers with the necessary skills to provide effective emotional and practical support. By addressing the critical role of families in cancer care, this study advocates for a more inclusive approach to treatment that considers not only the medical but also the psychosocial aspects of healing.